2010
DOI: 10.1042/bj20101310
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of substrate recognition and specificity of botulinum neurotoxin serotype F

Abstract: BoNTs (botulinum neurotoxins) are both deadly neurotoxins and natural toxins that are widely used in protein therapies to treat numerous neurological disorders of dystonia and spinal spasticity. Understanding the mechanism of action and substrate specificity of BoNTs is a prerequisite to develop antitoxin and novel BoNT-derived protein therapy. To date, there is a lack of detailed information with regard to how BoNTs recognize and hydrolyse the substrate VAMP-2 (vesicle-associated membrane protein 2), even tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 28 publications
(79 reference statements)
0
37
0
Order By: Relevance
“…Compared with substrate recognition by other serotypes of BoNT, LC/D possesses unique features of substrate recognition (14,15,20,21 , and Pro 154 ) of LC/D. Mutation of each residue to alanine or asparagine had no effect or only a minor effect on substrate hydrolysis, whereas triple mutations to alanine resulted in a much stronger reduction of substrate hydrolysis, highlighting the complementary effects of the three residues forming this pocket.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Compared with substrate recognition by other serotypes of BoNT, LC/D possesses unique features of substrate recognition (14,15,20,21 , and Pro 154 ) of LC/D. Mutation of each residue to alanine or asparagine had no effect or only a minor effect on substrate hydrolysis, whereas triple mutations to alanine resulted in a much stronger reduction of substrate hydrolysis, highlighting the complementary effects of the three residues forming this pocket.…”
Section: Discussionmentioning
confidence: 98%
“…The P1Ј site of VAMP-2 was shown to be important for LC/D substrate recognition, as seen in other serotypes of BoNT (14,15,20,21). Mutation of the VAMP-2 P1Ј residue (L60A) reduced LC/D substrate hydrolysis by ϳ25-fold.…”
Section: Dual Recognition Of the Vamp-2 P1 Site By The S1 Pocket Of Lc/dmentioning
confidence: 88%
See 1 more Smart Citation
“…Of these, subtype F7 was composed exclusively of BoNT F genes from Clostridium baratii strains [21]. Further studies showed that BoNT F exhibits a strict requirement for residues for substrate recognition that distinguishes BoNT F from other zinc endoproteases, including BoNTs A and B [22,23].…”
Section: Botulinum Neurotoxin Overviewmentioning
confidence: 99%
“…Plasmids for the expression of LC/T (1-436) and VAMP2 (1-97) and subsequent protein expression and purification were performed as previously described Chen, Wan). Site directed mutagenesis of pLC/T and pVAMP2 were performed using QuickChange (Stratagene) protocols as previously described .…”
Section: Plasmid Construction For Protein Expressionmentioning
confidence: 99%